India's Spatial Development - Desmet, Klaus; Ghani, Ejaz; O'Connell, Stephen; Rossi-Hansberg, Esteban (World Bank, Washington, DC, 2015)
This note examines the recent spatial development of India. Services, and to a lesser extent manufacturing, are increasingly concentrating in high-density clusters. This stands in contrast with the United States, where in the last decades services have tended to grow fastest in medium-density locations, such as Silicon Valley. Indias experience is not common to all fast-growing developing economies. The spatial growth pattern of China looks more similar to that of the United States than to that of India. What is preventing Indias medium-density cities from growing and taking full advantage of agglomeration forces? Future research should focus on identifying the barriers to growth in medium-density places. In the last two decades, the Indian economy has been growing at unprecedented rates, but that development has led to widening spatial disparities (Ghani 2010a). While some cities, such as Hyderabad, have become major high-tech hubs with world-class companies and real estate development reminiscent of Silicon Valley, many others remain mired in poverty and stagnation. Given the huge congestion in cities such as Mumbai or Kolkata, this seems to be a reasonable policy concern in the context of India. However, those cities also benefit from important agglomeration economies, so there is a need to analyze the trade-offs between the costs and benefits of economic density before articulating policy recommendations. Such an analysis should provide valuable insights into what types of spatial and regional policy interventions may be useful and effective. Compared to other countries at similar levels of development, Indias growth stems disproportionately from its burgeoning service sector (Ghani 2010b). The evidence of agglomeration in the U.S. service sector is in cities with densities of employment below 150 employees per square kilometer, while in India, evidence of agglomeration is found in cities with densities above this threshold. In other words, if the United States is used as the efficient benchmark, then 150 employees per square kilometer is the ideal density to take advantage of agglomeration economies. In India, however, these medium-density cities are the worst places. This suggests that the costs of congestion in India are either much smaller than in the United States, the agglomeration forces are much larger than in the United States, or that there are some frictions, policies, and a general lack of infrastructure in medium-density cities that prevent them from growing faster, therefore favoring concentration in high-density areas.